(untitled) (Global Journal of Human-Social Science, 2016)
The four core coordinates of human existence-culture, society, religion and familyhave continued in locating women and men in specific social contexts. Using a qualitative data collection approach, the study examines the context of married Yoruba women’s sexual and health rights focusing on their rights to make responsible sexual and reproductive decisions. Findings reveal interplay between gender and sexuality. Beliefs and images about masculinity and femininity result in the men feeling that they must initiate sex, dominate and conquer their wives, without being sensitive to their emotional needs. The logic that follows from this is the fact that men presumably are granted the unconditional sexual access to their wives, while women on the other hand lack sexual autonomy. The study concludes that there is relativity of power between married men and women in sexual intercourse no matter the level of the woman’s socioeconomic status instigated by the social conditioning.